2016
DOI: 10.1242/dmm.022145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bromocriptine alginate nanocomposite (BANC) on a transgenic Drosophila model of Parkinson's disease

Abstract: The effect of bromocriptine, a dopamine agonist, administered in the form of bromocriptine alginate nanocomposite (BANC) was studied on Parkinson's disease (PD) model flies. The synthesized BANC was subject to characterization and, at a final concentration of 0.5, 1.0 and 1.5 µM, was mixed in diet. The PD flies were allowed to feed on it for 24 days. A significant dose-dependent delay in the loss of climbing activity and activity pattern was observed in PD flies exposed to 0.5, 1.0 and 1.5 µM BANC. The PD flie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…The direct comparison results showed that the incidences of adverse reaction of ropinirole, piribedil, and bromocriptine were higher than other drugs, in the symptoms of somnolence, hallucination, dyskinesia, nausea, dizziness, and constipation. Due to the high affinities for the dopamine D2 and D3 receptors, dopamine agonist therapy may result in impulse control disorder through D3 receptors, and the dopamine agonists would cause side effects while acting anti‐Parkinson's functions . Ropinirole, as a nonergot dopamine receptor agonist, takes up an important position in the management of PD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct comparison results showed that the incidences of adverse reaction of ropinirole, piribedil, and bromocriptine were higher than other drugs, in the symptoms of somnolence, hallucination, dyskinesia, nausea, dizziness, and constipation. Due to the high affinities for the dopamine D2 and D3 receptors, dopamine agonist therapy may result in impulse control disorder through D3 receptors, and the dopamine agonists would cause side effects while acting anti‐Parkinson's functions . Ropinirole, as a nonergot dopamine receptor agonist, takes up an important position in the management of PD .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high affinities for the dopamine D2 and D3 receptors, dopamine agonist therapy may result in impulse control disorder through D3 receptors, and the dopamine agonists would cause side effects while acting anti-Parkinson's functions. 45 Ropinirole, as a nonergot dopamine receptor agonist, takes up an important position in the management of PD. 46 However, as shown in this study, it does produce a significant number of side effects such as dyskinesia and somnolence.…”
Section: Cumulative Probability Of Sortingmentioning
confidence: 99%
“…Nevertheless, there was no gross morphological change in the brains of PD flies. The results suggested that BANC is effective in reducing the PD symptoms in these transgenic flies (Siddique et al, 2016).…”
Section: Nanoparticle Applications In Neurodegenerative Diseases Nanomentioning
confidence: 87%
“…As a result, in comparison with the effectiveness of CeNC/IONC/MSN-T807 or MB alone, when both are combined to form a multifunctional nanocomposite, a synergistic therapeutic effect was achieved. Siddique et al (2016) studied the effect of alginate nanocomposite (BANC) on PD model flies. A significant decrease in lipid peroxidation and glutathione-S-transferase activity and an increase in glutathione content were observed in PD flies when exposed to BANC.…”
Section: Nanoparticle Applications In Neurodegenerative Diseases Nanomentioning
confidence: 99%
“…The pharmacological properties of various natural plant products using Drosophila as a model have been extensively reviewed by Panchal and Tiwari (2017). Our earlier studies using the same study model on flavonoids/ plant extracts (Fatima et al, 2017;Siddique et al, 2016;Siddique, Naz, Jyoti, 2014) have also shown the promising results in reducing the PD symptoms. Hence, it is concluded that the luteolin is potent in reducing the PD symptoms in transgenic Drosophila expressing human alpha synuclein in the neurons.…”
Section: Discussionmentioning
confidence: 99%